When Others Retire Early: What About Me? - Mollica, Kelly A.; DeWitt, Rocki-Lee (Academy of Management Journal, 2000)
We studied the reactions to an early retirement program of 668 employees of a large organization who were ineligible for the program. Specifically, we examined the influence of perceptions of the generosity of the organization's assistance to retirees (caretaking) on the remaining employees' intentions to quit. Findings contrasted with those from research on layoff survivors: perceptions of overly generous caretaking were associated with increased intentions to quit, particularly among more tenured employees.